Analisis Perbandingan Kinerja Keuangan Bank Aceh Sebelum dan Sesudah Konversi Syariah - Budianto Budianto; Dara Angreka Soufyan (Jurnal Akademi Akuntansi, 2021)
This study aims to compare the financial performance before and after the conversion from conventional to sharia systems at PT. Aceh Sharia Bank. Measurement of financial performance using the RGEC (Risk Profile, GCG, Earnings, Capital) method, where, Risk Profile is measured by the ratio of Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR), GCG is measured using a composite rating, Earnings using Return On Assets (ROA) and Return On Equity (ROE), while Capital is measured by the Capital Adequacy Ratio (CAR). The observations in this study used published financial statements for the three-year period before conversion (2013-2015) and three years after conversion (2016-2018). Testing the data analysis used the Paired Sample T-Test on a paired sample, while the data normality test used Shapiro-Wilk and Wilcoxon. Based on the results of analysis and testing, it is concluded that there are differences in financial performance before and after conversion as measured by the ratio of NPF and ROA. Meanwhile, the financial performance as measured by the ratio of FDR, ROE, CAR and GCG did not show significant differences.